Jointly acquired property of a working wife: A legal analysis from ’Urf perspective - Zainon, Masyitah Mohd; Bakar, Marina Abu; Zaghloul, Saad Gomaa Gomaa; Urus, Nur Sarah Tajul; Yusoff, Mus’ab Mohd; Azzis, Nadia Murshida Abd (Linguistics and Culture Review, 2021)
In Malaysia, jointly acquired property has been recognized due to divorce, polygamy, or death. Section 122 of the Islamic Family Law Enactment (State of Kedah Darul Aman) 2008, clearly provides the jurisdiction of Court in division of jointly acquired property. Disputes arose between Muslim’s scholars on the status of property of a working wife whether it can be regarded as a private property or jointly acquired property. Nowadays, it seems that the domestic contributions for a living are attributed to the property of the working wife. These contributions include the purchase of house, car, and expenses in upbringing the children. Therefore, the objective of this study is to identify the classification of property of the working wives and the condition of jointly acquired property that can be claimed by the husband from Islamic perspective and subsequently analyse the custom recognition on it. This study is a qualitative study in which data is collected from Islamic law books and legal sources. Data analysis completed by applying content analysis methods through a descriptive approach. The findings indicated that the custom (‘urf) recognized the classification of property of a wife to be accepted as jointly acquired property.